ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA TERHADAP PEMILIHAN KARIR SEBAGAI AKUNTAN PUBLIK (STUDI KASUS PADA MAHASISWA JURUSAN AKUNTANSI DI KOTA PADANG) - Elfiswandi Elfiswandi; Zerni Melmusi; Chlaudia Chanigia (Universitas Putera Batam, 2019)
The objective of this study was to analyze what the factors can influence students for choosing a career as a public accountant. Respondents of this study were students majoring in the accounting department in Padang, at private universities and state universities (University Putra Indonesia